Comparison of Sleep, Quality of Life, Anxiety and Depression Levels with Normal and Gestational Diabetes and Postpartum Results. - Dogan, Mirac; Dissiz, Melike (International Journal of Caring Sciences)
Objective: This study was conducted to compare the sleep, quality of life, anxiety and depression levels of pregnant women with and without gestational diabetes during pregnancy and to evaluate postpartum results in the postpartum period. Methods: The research was conducted as a comparative, descriptive and prospective study. The study was conducted with 60 of whom were diagnosed with gestational diabetes mellitus (GDM) and 60 of whom were not diagnosed with gestational diabetes mellitus. The data were obtained by face-to-face interview technique using the descriptive information form, Health-Related Quality of Life Questionnaire -36 (SF-36), Pittsburgh Sleep Quality Index (PSQI), Beck Anxiety Inventory (BAI), Edinburgh Postpartum Depression Scale (EPDS), and postpartum data collection forms. Results: It was determined that pregnant women with gestational diabetes had a significantly lower score in the field of mental health in the puerperal period (p<0.05). Nevertheless, the PSQI sleep latency score of pregnant women with gestational diabetes was found to be significantly lower compared to those without gestational diabetes (p<0.05). In the study, no significant difference was found in terms of Beck Anxiety Inventory scores of pregnant women with and without gestational diabetes in the pregnancy and puerperal periods (p>0.05). However, it was determined that pregnant women with diabetes in the puerperal period had significantly higher Edinburgh Postpartum Depression Scale scores compared to those without diabetes (p>0.05). Conclusion: In this study, it was determined that gestational diabetes negatively affected women's sleep, quality of life and depression levels.